2015
DOI: 10.1371/journal.pone.0117259
|View full text |Cite
|
Sign up to set email alerts
|

Contagion in Mass Killings and School Shootings

Abstract: BackgroundSeveral past studies have found that media reports of suicides and homicides appear to subsequently increase the incidence of similar events in the community, apparently due to the coverage planting the seeds of ideation in at-risk individuals to commit similar acts.MethodsHere we explore whether or not contagion is evident in more high-profile incidents, such as school shootings and mass killings (incidents with four or more people killed). We fit a contagion model to recent data sets related to suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
161
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(177 citation statements)
references
References 37 publications
10
161
1
1
Order By: Relevance
“…Similar guidelines could be developed and adopted by major media outlets for ethical reporting of mass shootings and similar events. Links between sensational reporting of mass shootings and copycat events are becoming better established (Cantor et al 1999, Towers et al 2015), and early proposals for media guidelines are already being developed (Perrin 2016). …”
Section: Toward Sound Policymentioning
confidence: 99%
“…Similar guidelines could be developed and adopted by major media outlets for ethical reporting of mass shootings and similar events. Links between sensational reporting of mass shootings and copycat events are becoming better established (Cantor et al 1999, Towers et al 2015), and early proposals for media guidelines are already being developed (Perrin 2016). …”
Section: Toward Sound Policymentioning
confidence: 99%
“…The infrequency with which homicide-suicide occurs poses several challenges. First, until now, researchers have mainly discounted the utility of studying homicide-suicide as a distinct behavior, instead regarding it as a variant of either homicide or suicide and studying it accordingly (Liem & Nieuwbeerta, 2010), despite the knowledge that homicide-suicide has a devastating impact on families and communities (Liem, 2010), garners national attention that can be used to shape the sociopolitical landscape (McPhedran et al, 2015), and inspires copycat crimes (Towers, Gomez-Lievano, Khan, Mubayi, & Castillo-Chavez, 2015). Second, and relatedly, many studies on homicide-suicide have methodological and statistical shortcomings, including small sample sizes, low statistical power, inflated effect sizes, overestimation of both type I and type II errors, inefficiency of model estimates, and low reproducibility of results (Button et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, we documented an increase where there were 154 episodes in a 3-year span as compared with 44 incidents from 1966 to 2008 in the USA. This spike in school shooting may be explained by the theory of contagion; evidence has shown that mass killings involving firearms are motivated by similar events in the immediate past 31. To our knowledge, there has been no formal documentation of the spatial or temporal spread of school shooting episodes after Sandy Hook Elementary shooting.…”
Section: Discussionmentioning
confidence: 97%